Parent-to-parent support for the families of deaf children identified by the newborn hearing screen. (2nd April 2020) - Mehta, Kinjal; Hilton, Enid; Baldwin, Margaret; Watkin, Peter
ABSTRACT: Parent-to-parent support for the families of deaf children has been provided in an East London district as an adjunct to the existing Early Support programme. Two parents of deaf children were employed as Parent Support Workers. They were members of a multi-disciplinary team of audiologists, teachers of the deaf and a specialist speech therapist. A questionnaire was used to obtain the views of the parents of a 10-year cohort of 35 deaf children who had received the peer support. There were high levels of satisfaction. Twenty-two respondents (63%) judged that a parent who had a shared experience was the person best placed to offer help and advice immediately following the diagnosis of childhood deafness with 27 (77%) considering the counselling and guidance of the teacher or therapist as most useful in the pre-school period after this initial period. An overwhelming 34 (97%) would recommend peer support as being useful. Twelve professionals, including five teachers, submitted free text on their views of the support. This was evaluated using thematic analysis. There were concerns about training and governance of the Parent Support Workers, with one teacher considering that the role may conflict with that of the teacher. However, ten professionals considered it to be a beneficial addition to existing programmes and none wanted it withdrawn. Most recognised that the "shared experience" of caring for a deaf child enabled the support workers to get close to families and provide a link with the home, which helped the parents engage with the intervention of the multi-disciplinary team.